LIFETIME RISKS FOR CARDIOVASCULAR DISEASE MORTALITY BY CARDIORESPIRATORY FITNESS LEVELS MEASURED AT AGE 45-, 55-, AND 65-YEARS IN MEN: THE COOPER CENTER LONGITUDINAL STUDY - Berry, Jarett D. (2011)
OBJECTIVES: To determine the association between fitness and lifetime risk for cardiovascular disease (CVD). BACKGROUND: Higher levels of traditional risk factors are associated with marked differences in lifetime risks for CVD. However, data are sparse regarding the association between fitness and the lifetime risk for CVD. METHODS: We followed 11,049 men who underwent clinical examination at the Cooper Clinic in Dallas, TX before 1990 until the occurrence of CVD death, non-CVD death, or attainment of age 90 (281,469 person-years of follow-up, median follow-up 25.3 years, 1,106 CVD deaths). Fitness was measured by Balke protocol and categorized according to treadmill time into low-, intermediate-, and high- fitness with further stratification by CVD risk factor burden. Lifetime risk for CVD death determined by the National Death Index was estimated for fitness levels measured at ages 45-, 55-, and 65-years with non-CVD death as the competing event. RESULTS: Differences in fitness levels (low- fitness versus high- fitness) were associated with marked differences in the lifetime risks for CVD death at each index age (age 45: 13.7% versus 3.4%; age 55: 34.2% versus 15.3%; age 65: 35.6% versus 17.1%). These associations were strongest among individuals with CVD risk factors. CONCLUSIONS: A single measurement of low fitness in mid-life was associated with higher lifetime risk for CVD death, particularly among individuals with a high burden of CVD risk factors.